A clinical study of viral hepatitis in children: a prospective hospital-based study - N., Girish; B., Sunil; Devaranavadagi, Ranganatha A. (International Journal of Contemporary Pediatrics, 2018)
Background: Viral hepatitis is a major public health issue throughout the world affecting millions of children; Clinical presentation may vary from asymptomatic to hepatitis, cirrhosis, liver failure and cancer. This study is aimed at understanding the clinical profile of viral hepatitis in children. Methods: Prospectively, 48 children admitted in paediatric unit with confirmed viral hepatitis from August 2015 to July 2016 at KIMS hospital, Bangalore were included. In each case, age, sex, clinical presentation and laboratory investigations were collected and analysed. Results: Out of 48 patients, 26 were girls and 22 were boys. Out of which 40 cases were positive for IgM Hepatitis A, 1 case of HbsAg positive, 7 cases were non-A non B Hepatitis. All cases presented with fever (100%), jaundice found in 40 cases (83.3%), 33 cases had abdominal pain (68.7%), vomiting was present in 40 cases (83.7%), 34 cases presented with dark colored urine (70.8%), altered sensorium in 3 cases (6.2%). Icterus was found in 48 (100%) cases, pallor was found in 17 cases (35.4%), Ascitis in 8 cases (16.7%), hepatomegaly in 37 cases (76%), oedema in 10 cases (21%). Liver enzymes elevated at admission in almost all cases, 16 cases had SGPT b/w 200-500. 10 cases had SGPT b/w 500-1000, 19 cases had SGPT b/w 1000-3000 and 2 cases had SGPT of more than 3000. 18 cases had total bilirubin between 5-10 mg/dl, 6 cases had total bilirubin >10 mg/dl. 44 cases had PT <1.5 at admission, 1 case had PT INR between 1.5-2.5, 1 case had INR between 2.5-3.5, 2 cases had INR>3.5. Out of 48 cases 2 cases died. Out of 2 deaths, 1 case of hepatitis A and 1 case positive for Hepatitis B. The cause of death was hepatic encephalopathy in both the cases. Conclusions: Majority of cases in children were hepatitis A cases, followed by non-A non B. Most of the cases were aged above 3 years with slight girl’s predominance. Those cases with elevated liver enzymes (SGOT >3000) and those with PT INR >3 at admission has higher mortality.